2019
DOI: 10.1097/aln.0000000000002488
|View full text |Cite
|
Sign up to set email alerts
|

Major Adverse Cardiac Events and Mortality Associated with Electroconvulsive Therapy

Abstract: EDITOR’S PERSPECTIVE What We Already Know about This Topic The incidence of major adverse cardiac events after electroconvulsive therapy is not known What This Article Tells Us That Is New Major adverse cardiac events and death after electroconvulsive therapy are infrequent and occur in about 1 of 50 patients and after about 1 of 200 to 500 electroconvulsive therapy treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…A large study of case records of patients who died from natural causes within a month of ECT showed no association with ECT treatment (total n = 99,728 treatments) (Ostergaard et al, 2014). Two meta-analyses (Duma et al, 2019; Torring et al, 2017) and recent cohort studies (Blumberger et al, 2017; Dennis et al, 2017) have shown that ECT is associated with a low likelihood of immediate or short-term death, and the few available studies have indicated that patients treated with ECT compared to other patients have decreased long-term mortality from all, and natural, causes (Avery and Winokur, 1976; Munk-Olsen et al, 2007; Philibert et al, 1995). However, no studies have examined whether depression severity influences the effect of ECT on health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A large study of case records of patients who died from natural causes within a month of ECT showed no association with ECT treatment (total n = 99,728 treatments) (Ostergaard et al, 2014). Two meta-analyses (Duma et al, 2019; Torring et al, 2017) and recent cohort studies (Blumberger et al, 2017; Dennis et al, 2017) have shown that ECT is associated with a low likelihood of immediate or short-term death, and the few available studies have indicated that patients treated with ECT compared to other patients have decreased long-term mortality from all, and natural, causes (Avery and Winokur, 1976; Munk-Olsen et al, 2007; Philibert et al, 1995). However, no studies have examined whether depression severity influences the effect of ECT on health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In discussing the mortality rate after ECT the authors of this review dismiss a recent meta-analysis of 15 studies finding low rates as a ‘study’ (not acknowledged as a meta-analysis) ‘based on medical records (relying on staff recording that [ECT treatments] had caused a death)’. One has to then ask why they did not instead report a meta-analysis of all-cause mortality after ECT based on data from 43 studies (Duma 2019). This found a mortality rate of 0.42/1000 patients and 6/100 000 ECT treatments, not all of which would be due to ECT, as depression itself is associated with a 1.5–2 times higher risk of death than in the general population.…”
Section: Beyond the Systematic Reviewmentioning
confidence: 99%
“…There is reasonable agreement, however, that the leading cause of death is cardiovascular failure. A recent review of 82 studies found that one in 50 patients experience ‘major adverse cardiac events’ (Duma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%